Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00167-012-1882-0
|View full text |Cite
|
Sign up to set email alerts
|

Clamp fixation to prevent unfolding of a suture knot decreases tensile strength of polypropylene sutures

Abstract: Under microscopic examination, polypropylene sutures were found to be deformed by clamp fixation, while the others were not. Polypropylene sutures can be easily damaged when it is fixed by a clamp during knot tying. Presented data demonstrated that in real surgical situations clamp fixation of polypropylene knots can damage the suture loop and carry the risk of acute failure of repair site during early rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…One possible explanation could be random error due to, for instance, the quality of the underlying initial two knots, though the effect of such errors should have been eliminated considering the 60 trials performed in the study (p = 0.01). On the other hand, similar findings have also been reported in literature, where the knot quality does not appear to be the function of a sole variable consisting of magnitude of the pulling force [51], [52]. Hence, the underlying reason for this observation may lie in the way the suture's structure fails under excessive load.…”
Section: Discussionsupporting
confidence: 85%
“…One possible explanation could be random error due to, for instance, the quality of the underlying initial two knots, though the effect of such errors should have been eliminated considering the 60 trials performed in the study (p = 0.01). On the other hand, similar findings have also been reported in literature, where the knot quality does not appear to be the function of a sole variable consisting of magnitude of the pulling force [51], [52]. Hence, the underlying reason for this observation may lie in the way the suture's structure fails under excessive load.…”
Section: Discussionsupporting
confidence: 85%
“…When we are confronted with a high-tension closure, the usual practice is clamping the first throw with the help of an assistant. The results of Mehmet's research demonstrated that the ultimate failure load of the monofilament nonabsorbable polypropylene suture was significantly decreased when the first throw was fixed with a clamp to prevent slippage; however, monofilament polyglyconate, nylon, and braided absorbable polyglactin sutures were not affected by fixing the first throw (5). According to Bisson's study, the UTL was reduced in No.…”
Section: Discussionmentioning
confidence: 99%
“…However, this usual practice has certain deficiencies. First, clamp fixation to prevent unfolding of the first suture knot may damage the suture and decrease its tensile strength (5)(6)(7)(8). Second, the first suture knot may slide leading to a small Original Article gap formation when the clamp is removed.…”
Section: Introductionmentioning
confidence: 99%
“…The crimp generates friction on the leader line, increasing load and stiffness while decreasing elongation . The interface where the nylon exits the crimp clamp is a vulnerable point due to the stress riser effect, similar to a knot . The use of double‐loops and double‐crimp clamps has also been recommended for enhanced strength of repair …”
mentioning
confidence: 99%
“…When making a square knot, the practice of clamping the first throw with an instrument to prevent loss of tension can damage the material and reduce its tensile strength. Turker et al reported that polypropylene had significantly lower ultimate failure load when the first throw was clamped; however, nylon was not affected by fixing the first throw . The tube knot (TB; Figs and ) is a low‐profile, flat knot made using a large gauge, preferably blunt, hypodermic needle to act as the tube, and is based on a fly fishing knot known as the nail knot (http://www.netknots.com/fishing_knots/nail-knot/).…”
mentioning
confidence: 99%